Penerapan e-SPTPD dalam Pelaporan Pajak Barang dan Jasa Tertentu atas Jasa Perhotelan di Kabupaten Kediri - Ajeng Siska Wulandari (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This Real Work Practice aims to examine the implementation of e-SPTPD (Electronic Local rax Return) in reporting Certain Goods and Services Tax (PBJT) On Hotel Services at the Regional Revenue Agency (Bapenda) of Kediri Regency. Conducted for 52 working days from February 6 Io April 30, 2026, the aulhor was placed in the data collection and assessment division. Data welt' collected thmugh interviews, observations, documentation, and literature studies, using both quantitative and qualitative appmaches with primary and secondary data sources. The implementation is based on Regional Regulation No. 9 of 2025 and Regent Regulation No. 81 of 2024. wquiring eleclmonic SPTPD submission no later Ihan 15 working days after the tax period ends. The e-SPTPD process covers online NPWPD legistration, system login, tax object selection, tax yeportfilling, 'evenue document upload, and Virtual Account payment. A total 14 tar objects woe megisteled between 2021 and 2025, with PBJT-Hote/ dominating at 78.6%, and 25 taxpayers overall aclively reported via e-SPTPD duoughour 2025, with PBJT-Horel dominating at 80%. Revenue realization 2021—2024 consistently exceeded tmgets, but in 2025 only leached 96.42% o/ the target. Despite impmved administrative efficiency, obstacles '?main, including network disruptions, undetected payments, umeporled zem-ævenue conditions, forgotten account cwdentials, and the absence efa tapping for the hotel secto/; leaving revenue accuracy supenisionfully reliant on the self-assessment system.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: e-SPTPD; Certain Goods and Services Tax; Bapenda Kediri Regency